2023
DOI: 10.3201/eid2904.221878
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus 2 and Human Adenovirus F41 in Wastewater during Outbreak of Severe Acute Hepatitis in Children, Ireland

Abstract: Organization (WHO) received reports of 1,010 probable cases of severe acute hepatitis of unknown etiology (SAHUE) in young children from 35 countries (1). Many cases resulted in severe clinical outcomes; ≈5% of patients required liver transplants, and 22 died. Most (48%) cases were reported from the WHO European Region, and 484 cases were reported in previously healthy children from 21 countries (1). Ireland reported 28 probable cases of SAHUE in non-A-E hepatitis, including 2 patients who received liver trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…These limitations make estimating disease occurrence (incidence or prevalence) in the sewersheds of the WWTPs from positivity rate data difficult. Martin et al ( 28 ) and Reyne et al ( 29 ) reported that concentrations of HAdV F41 in wastewater influent in Ireland correlated with laboratory confirmed adenovirus F41 infections. Huang et al ( 30 ) summarized studies relating HuNoV in wastewater influent and primary effluent to measures of disease occurrence, and Boehm et al ( 7 ) reported similar correlations between HuNoV GII in solids to positivity rates using different data.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations make estimating disease occurrence (incidence or prevalence) in the sewersheds of the WWTPs from positivity rate data difficult. Martin et al ( 28 ) and Reyne et al ( 29 ) reported that concentrations of HAdV F41 in wastewater influent in Ireland correlated with laboratory confirmed adenovirus F41 infections. Huang et al ( 30 ) summarized studies relating HuNoV in wastewater influent and primary effluent to measures of disease occurrence, and Boehm et al ( 7 ) reported similar correlations between HuNoV GII in solids to positivity rates using different data.…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of human mastadenovirus F40 and F41 corroborated with other studies, revealing the predominance of these types circulating in clinical samples in Brazil [ 93 , 94 , 95 ]. Recently, the F41 serotype was detected in wastewater samples in Ireland [ 96 ], Australia [ 97 ], the UK [ 98 ], and Japan [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that there is, indeed, an increased incidence of acute, severe hepatitis of unknown origin in children but several factors could trigger it, one of which could be HAdV-F41 and/or AAV-2 [ 189 ]. For example, an increase in HAdV-F41 and AAV-2 occurrences has been observed in wastewater in Northern Ireland, coincident with an increase in severe hepatitis in young children [ 190 , 191 ]. Although there was an increase in HAdV-F41 at the same time as the increase in hepatitis, the levels of other adenoviruses in the wastewater stayed approximately constant [ 190 ].…”
Section: Adenovirus F41 and Acute Severe Childhood Hepatitismentioning
confidence: 99%